Essays on conglomerate mergers - Garcia, Carolina Policarpo (2018)
This thesis takes advantage of a wave of mergers and acquisitions in the Brazilian higher education industry to provide evidence on the potential effects of conglomerate mergers, particularly market extension mergers. The first chapter is devoted to assess the effects of such mergers on tuition fees, enrollment rate and quality indicators. The richness of the dataset allows to disentangle the effects of conglomerate mergers and horizontal mergers, showing that both types of mergers impact acquired institutions, but in different ways. The second chapter evaluates the effects of the ownership changes on the labor market of professors, focusing on wages, total number of faculty, workload and the likelihood of contract termination after the acquisition. The last chapter analyzes the determinants of choice in higher education, focusing on estimating to which extent educational groups and brand names influence the choice of potential students. Results show that conglomerate mergers raise efficiency on acquired units and the gains may be partially shared with students, in the form of an increased number of freshmen, and professors, by means of higher wages. These efficiences may come through higher student-faculty ratios, standardized courseware between the units of the group, extensive use of online content in substitution to in-class activities and the centralization of the management and financial activities in a shared services center. Educational groups attract a great number of potential students and have an important role in increasing access to higher education. The ability to recruit potential students may come from international network benefits, attractive prices, funding availability, better quality indexes and brand awareness. Importantly, each educational group has its own strategy when combining these elements and not all of them must be present. The results also highlight the role of government and regulatory constraints in the sector. The first and most obvious consequence is the high number of mergers and acquisitions that took place to avoid the requirements to entry organically in local markets. Second, the availability of public student loans greatly determines the access to higher education. Third, as the students' willingness to pay for higher quality programs is low, the educational groups closely follow the minimum requirements for the quality indexes.